2016
DOI: 10.4067/s0034-98872016000100012
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados paliativos en personas con demencia severa: reflexiones y desafíos

Abstract: Dementia is an important public health problem due to the complex challenges it poses during the progression of the disease and especially during its end-of-life stage. The aim of this article is to consider the issues that arise from the use of commonly administered therapies in patients with severe dementia. Scenarios where excessive or futile therapeutic interventions might occur are discussed. The article concludes that it is advisable to analyze the clinical criteria and ethical considerations related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
1
0
10
Order By: Relevance
“…It has been reported that in the last 3 months of survival, 37.3% of patients suffered from pneumonia, 32.2% had a fever, and 90.4% displayed swallowing disorders. Pneumonia has been identified as the complication most frequently leading to death (Mitchell et al, 2009; for a review, see Slachevsky et al, 2016). …”
Section: Dementia-related Mortalitymentioning
confidence: 99%
“…It has been reported that in the last 3 months of survival, 37.3% of patients suffered from pneumonia, 32.2% had a fever, and 90.4% displayed swallowing disorders. Pneumonia has been identified as the complication most frequently leading to death (Mitchell et al, 2009; for a review, see Slachevsky et al, 2016). …”
Section: Dementia-related Mortalitymentioning
confidence: 99%
“…El dolor pertenece al orden de lo somático, de lo orgánico; mientras que el sufrimiento está más relacionado con la esfera psicológica, este evoca dimensiones más profundas del ser humano. Se puede sufrir sin dolor físico (17,(43)(44)(45) .…”
Section: Otros Cuidadoresunclassified
“…Los equipos interdisciplinarios de CP ofrecen atención integral al paciente y acompañamiento a la familia/ cuidadores que requieren apoyo, así como las herramientas para no solo cuidar, sino para aceptar el proceso de morir y desarrollar el duelo correspondiente, evitando la obstinación terapéutica o la prolongación de la vida, e ignorando el bienestar del paciente y la familia (42)(43)(44)46) . La nutrición e hidratación artificiales se refiere a la administración de nutrientes y agua a través de las vías gastrointestinal (enteral) o intravenosa (parenteral).…”
Section: Otros Cuidadoresunclassified
“…Cabe reiterar que la responsabilidad del profesional de la salud implica la necesidad de reconocer en el paciente a una persona que no solo le refleja un trastorno en su conducta, sino que también tiene una vida y se desempeña en un grupo social determinado. Por tanto, el paciente es un agente autónomo y requiere ser tratado con dignidad (40). Considerando las implicaciones de los tca, es necesario que la atención se geste dentro de un marco ético en el que los valores y principios del profesional y del paciente sean considerados y respetados por igual.…”
Section: Implicaciones éTicas De Los Tca En El Actuar De Los Profesionales De La Saludunclassified